The hype over Hyperbolic Browsers - Maryellen Mott Allen (Online, 2002)
Considers complaints about the usability in the human-computer interaction aspect of information retrieval and discusses information visualization, the Online Library of Information Visualization Environments, hyperbolic information structure, subject searching, real-world applications, relational databases and hyperbolic trees, and the future of visual information structures.